2021
DOI: 10.1111/jce.15151
|View full text |Cite
|
Sign up to set email alerts
|

Stepwise endo‐/epicardial catheter ablation for atrial fibrillation: The Mediterranea approach

Abstract: Background: Outcomes of catheter ablation (CA) among patients with nonparoxysmal atrial fibrillation (AF) are largely disappointing.Objective: We sought to evaluate the feasibility, effectiveness, and safety of a single-stage stepwise endo-/epicardial approach in patients with persistent/ longstanding-persistent AF.Methods: We enrolled 25 consecutive patients with symptomatic persistent (n = 4) or longstanding-persistent (n = 21) AF and at least one prior endocardial procedure, who underwent CA using an endo-/… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

1
26
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(28 citation statements)
references
References 31 publications
1
26
0
1
Order By: Relevance
“…In our work, we provided the first description of a novel stepwise approach for longstanding persistent AF, the Mediterranea technique, which critically differs from previously proposed procedures in that it incorporates epicardial ablation of epicardial arrhythmogenic structures (namely, the Bachmann's bundle and the ligament of Marshall). 1 In our first report, we were only able to enroll a limited number of patients (n=25) and to follow them for approximately nine months, therefore our work may well be considered a pilot study. 1 At the prespecified one-year follow-up appointment, we did not observe any further recurrences, so that freedom from arrhythmia recurrences measured 88% (22 out of 25) after approximately 12 months.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In our work, we provided the first description of a novel stepwise approach for longstanding persistent AF, the Mediterranea technique, which critically differs from previously proposed procedures in that it incorporates epicardial ablation of epicardial arrhythmogenic structures (namely, the Bachmann's bundle and the ligament of Marshall). 1 In our first report, we were only able to enroll a limited number of patients (n=25) and to follow them for approximately nine months, therefore our work may well be considered a pilot study. 1 At the prespecified one-year follow-up appointment, we did not observe any further recurrences, so that freedom from arrhythmia recurrences measured 88% (22 out of 25) after approximately 12 months.…”
mentioning
confidence: 99%
“…1 In our first report, we were only able to enroll a limited number of patients (n=25) and to follow them for approximately nine months, therefore our work may well be considered a pilot study. 1 At the prespecified one-year follow-up appointment, we did not observe any further recurrences, so that freedom from arrhythmia recurrences measured 88% (22 out of 25) after approximately 12 months. Therefore, our results seem very promising when compared to other hybrid techniques mainly involving posterior wall isolation.…”
mentioning
confidence: 99%
“…Periods of observation following combined epicardial and endocardial ablation for non-paroxysmal atrial fibrillation: Navigating the sea of hybrid convergent procedures De Martino et al reported their experience with a stepwise endocardial and epicardial catheter ablation strategy for treatment of non-paroxysmal atrial fibrillation (AF) using a single-center, singlearm prospective cohort design. 1 Named the Mediterranea approach, it resulted in 22 of 25 (88%) patients experiencing freedom from any AF or atrial tachycardia, excluding the 3-month postablation "blanking period," after a median follow-up of 266 days (interquartile range, 96 days). The primary effectiveness outcome was analyzed using the Kaplan-Meier method and, consequently, did not incorporate a prespecified time point for assessment of arrhythmia status.…”
mentioning
confidence: 99%
“…Investigators concluded their approach "resulted in restoration and maintenance of sinus rhythm in the majority of patients at 9month follow-up." 1 As illustrated in survival curves presented in the CONVERGE trial, which assessed 12-month outcomes after hybrid convergent procedures where unipolar radiofrequency devices (EPi-Sense; AtriCure) were used for epicardial ablation, the 9-month time point corresponds to follow-up day 275. 2 Therefore, in the published article, the majority of patients that received the Mediterranea approach had not yet reached the 9-month postablation time point.…”
mentioning
confidence: 99%
See 1 more Smart Citation